Molding sand with adjustable refractoriness and cooling speed

By adding different proportions of iron sand and waste high-aluminum brick particles to the molding sand, combined with an appropriate amount of binder and add-ons, molding sand with adjustable refraction resistance and cooling speed is prepared, which solves the problem that existing molding sand cannot meet the needs of different castings and improves casting quality and production efficiency.

CN119794256AInactive Publication Date: 2025-04-11JIANGSU ZHONGXIN FOUNDRY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311304207.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The fire resistance and cooling speed of existing molded sand cannot be adjusted, making it difficult to meet the high-quality casting needs of different castings.

Method used

By adding different proportions of iron sand and waste high-aluminum brick particles to the molded sand, combined with binders and add-ons such as phenolic resin, water glass and clay, coated sand, water glass sand and clay sand are prepared to achieve adjustability of the molded sand’s refraction and cooling speed.

Benefits of technology

The refractory resistance and cooling speed of molded sand are adjusted, and the properties of molded sand can be adjusted according to the requirements of the castings, thereby improving the quality of the castings and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of molding sand, and discloses molding sand with adjustable refractoriness and cooling speed, the molding sand with adjustable refractoriness and cooling speed specifically comprises quartz sand, iron sand, waste high alumina brick particles, a binder and an additive; the binder is specifically composed of one or more of phenolic resin, water glass and clay; the additive specifically comprises one or more of urotropine, calcium stearate, silane, ethylene glycol diethyl ester, yellow dextrin, sodium carbonate, pulverized coal, water, calcium stearate, bentonite and sodium carbonate. According to the molding sand with the adjustable refractoriness and cooling speed, in the casting process, the iron sand and the waste high-alumina brick particles in different proportions can be added according to casting requirements to adjust the performance of the molding sand, the iron sand can adjust the cooling capacity of the molding sand, and the waste high-alumina brick particles improve the refractoriness of the molding sand; the molding sand has the functions of adjusting the refractoriness and the cooling speed, and the problem that high-quality castings are difficult to obtain through existing single molding sand is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molding sand, in particular to molding sand with adjustable refractoriness and cooling speed. Background Art

[0002] Molding sand is the main material in the casting process and is also the key material for obtaining high-quality castings. According to statistics, 50% to 70% of the defects of castings in sand casting are related to molding sand. Therefore, it is particularly important to improve the quality of molding sand, especially to improve the compatibility of molding sand and castings.

[0003] At present, foundries basically use the same formula of molding sand for castings of the same material, such as cast steel molding sand, cast iron molding sand, cast nonferrous alloy molding sand, etc. However, in the actual production process, although the same material is used, the shape, wall thickness, and metallographic structure requirements of the castings are different. Sometimes it is difficult to obtain high-quality castings with a single molding sand. For example, castings with thinner walls require a slow cooling rate; castings with thicker walls require a fast cooling rate and high refractoriness of the molding sand; for cast iron parts, high pearlite content in the metallographic structure requires a fast cooling rate; for steel castings, high refractoriness of the molding sand is required. Simply improving the performance of the molding sand will increase production costs. For this reason, we propose a molding sand with adjustable refractoriness and cooling rate to solve the above technical problems. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a molding sand with adjustable refractoriness and cooling rate, which has the advantages of being able to adjust the refractoriness and cooling rate according to the requirements of the casting, and solves the problem that the refractoriness and cooling rate of the existing materials cannot be adjusted.

[0005] In order to achieve the above-mentioned purpose of adjusting the refractoriness and cooling rate according to the requirements of the casting, the present invention provides the following technical solutions: a molding sand with adjustable refractoriness and cooling rate, specifically composed of: quartz sand, iron sand, waste high-alumina brick particles, a binder and additives; The binder specifically consists of: one or more of phenolic resin, water glass and clay; The additive specifically consists of: one or more of urotropine, calcium stearate, silane, ethylene glycol diethyl ester, yellow dextrin, sodium carbonate, coal powder, water, calcium stearate, bentonite and sodium carbonate; According to the different binders and additives added, the above materials can be combined into coated sand, water glass sand and clay sand; The waste high-alumina bricks are high-alumina bricks discarded after industrial kilns are replaced. They are crushed into particles and then placed in a drum for processing, so that the waste high-alumina brick particles collide and rub against each other, making the particles polygonal or round in shape, and then sieving to obtain the required particle size.

[0006] Preferably, the weight ratio of the coated sand is: 100 parts of quartz sand, 0-50 parts of iron sand, 2-40 parts of waste high-alumina brick particles, 3-7 parts of phenolic resin, 0.04-0.06 parts of silane, 0.6-1.2 parts of urotropine and 0.3-0.45 parts of calcium stearate.

[0007] Preferably, the weight ratio of the water glass sand is: 100 parts of quartz sand, 0-50 parts of iron sand, 2-40 parts of waste high-alumina brick particles, 3-7 parts of water glass, 0.1-0.5 parts of ethylene glycol diethyl ester and 1.0-2.0 parts of yellow dextrin.

[0008] Preferably, the weight ratio of the clay sand is: 100 parts of quartz sand, 0-50 parts of iron sand, 10-40 parts of waste high-alumina brick particles, 4-6 parts of bentonite, 0.1-0.05 parts of sodium carbonate, 3-6 parts of coal powder and 3.5-5 parts of water content.

[0009] Preferably, the weight ratio of the molding sand is: 100 parts of quartz sand, 0 parts of iron sand, 30 parts of waste high-alumina brick particles, 3 parts of phenolic resin, 0.04 parts of silane, 0.6 parts of urotropine and 0.3 parts of calcium stearate.

[0010] Preferably, the weight ratio of the molding sand is: 100 parts of quartz sand, 30 parts of iron sand, 30 parts of waste high-alumina brick particles, 4 parts of phenolic resin, 0.05 parts of silane, 0.7 parts of urotropine and 0.4 parts of calcium stearate.

[0011] Preferably, the weight ratio of the molding sand is: 100 parts of quartz sand, 25 parts of iron sand, 40 parts of waste high-alumina brick particles, 6 parts of water glass, 0.2 parts of ethylene glycol diethyl ester and 1 part of yellow dextrin.

[0012] Preferably, the weight ratio of the molding sand is: 100 parts of quartz sand, 0 parts of iron sand, 10 parts of waste high-alumina brick particles, 4 parts of bentonite, 0.05 parts of sodium carbonate, 4 parts of coal powder and 4.5 parts of water content.

[0013] Preferably, the weight ratio of the molding sand is: 100 parts of quartz sand, 40 parts of iron sand, 20 parts of waste high-alumina brick particles, 6 parts of bentonite, 0.1 parts of sodium carbonate, 4 parts of coal powder and 3.5 parts of water content.

[0014] Preferably, the preparation steps are as follows: Step 1: Mix quartz sand and waste high-alumina brick particles and heat them to 140-160°C; Step 2: Put the hot sand into the sand mixer and slowly add phenolic resin for 30 to 50 seconds; Step 3: Add silane for 10 seconds; Step 4: Add urotropine aqueous solution, the ratio of urotropine to water is 1:1, and the time is 30 seconds; Step 5, add calcium stearate, continue mixing and grinding, and cool to 40°C; Step 6: After crushing and screening, set aside.

[0015] Compared with the prior art, the present invention provides a molding sand with adjustable refractoriness and cooling speed, which has the following beneficial effects: 1. The present invention can adjust the performance of the molding sand by adding different proportions of iron sand and waste high-aluminum brick particles according to the requirements of the casting during the casting process. The iron sand can adjust the cooling capacity of the molding sand, and the waste high-aluminum brick particles improve the refractoriness of the molding sand, so that the molding sand has the functions of adjusting the refractoriness and cooling speed, thereby solving the problem that it is difficult to obtain high-quality castings with the existing single molding sand.

[0016] 2. Compared with the conventional method of adding magnesia sand to the molding sand, the present invention improves the high temperature resistance of the molding sand by adding waste high alumina brick particles to the molding sand. Since magnesia sand is alkaline, it is easy to react with acidic quartz sand at high temperature to form a low melting point substance, and the main component of high alumina brick is Al 2 O 3 It is neutral and does not react with quartz sand, effectively improving the high temperature resistance of molding sand. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram of the process for preparing coated sand according to the present invention; Figure 2 This is a schematic diagram of the preparation process of water glass sand of the present invention; Figure 3 The figure is a schematic diagram of the clay sand preparation process of the present invention. Implementation

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Due to the different requirements for castings in the actual production process, the existing molding sand material has a single performance and cannot meet the casting of high-quality castings. Based on this, we propose a molding sand with adjustable refractoriness and cooling speed to meet the casting needs of different castings. The specific plan is as follows: A molding sand with adjustable refractoriness and cooling speed, specifically composed of: quartz sand, iron sand, waste high-alumina brick particles, a binder and additives; The binder specifically consists of: one or more of phenolic resin, water glass and clay; The additive specifically consists of: one or more of urotropine, calcium stearate, silane, ethylene glycol diethyl ester, yellow dextrin, sodium carbonate, coal powder, water, calcium stearate, bentonite and sodium carbonate; According to the different binders and additives added, the above materials can be combined into coated sand, water glass sand and clay sand; The weight ratio of the coated sand is: 100 parts of quartz sand, 0-50 parts of iron sand, 2-40 parts of waste high-alumina brick particles, 3-7 parts of phenolic resin, 0.04-0.06 parts of silane, 0.6-1.2 parts of hexamethylenetetramine and 0.3-0.45 parts of calcium stearate; The weight ratio of water glass sand is: 100 parts of quartz sand, 0-50 parts of iron sand, 2-40 parts of waste high-alumina brick particles, 3-7 parts of water glass, 0.1-0.5 parts of ethylene glycol diethyl ester and 1.0-2.0 parts of yellow dextrin; The weight ratio of clay sand is: 100 parts of quartz sand, 0-50 parts of iron sand, 10-40 parts of waste high-alumina brick particles, 4-6 parts of bentonite, 0.1-0.05 parts of sodium carbonate, 3-6 parts of coal powder and 3.5-5 parts of water content.

[0020] Waste high-alumina bricks are high-alumina bricks discarded after industrial kilns are replaced. They are crushed into particles and then put into a drum for processing, so that the waste high-alumina brick particles collide and rub against each other, so that the particle shape is polygonal or round, and then the required particle size is obtained by screening. The present invention adds waste high-alumina brick particles to the molding sand. Compared with the method of adding magnesia sand to the molding sand to improve the high-temperature resistance of the molding sand, magnesia sand is alkaline and easily reacts with acidic quartz sand at high temperature to form a low melting point substance, and the main component of high-alumina bricks is Al 2 O 3 It is neutral and does not react with quartz sand, effectively improving the high temperature resistance of molding sand.

[0021] The following are specific embodiments: Example 1

[0022] The weight ratio of the molding sand is: 100 parts of quartz sand, 0 parts of iron sand, 30 parts of waste high-alumina brick particles, 3 parts of phenolic resin, 0.04 parts of silane, 0.6 parts of hexamethylenetetramine and 0.3 parts of calcium stearate; The preparation steps are: Step 1: Mix quartz sand and waste high-alumina brick particles and heat them to 140-160°C; Step 2: Put the hot sand into the sand mixer and slowly add phenolic resin for 30 to 50 seconds; Step 3: Add silane for 10 seconds; Step 4: Add urotropine aqueous solution, the ratio of urotropine to water is 1:1, and the time is 30 seconds; Step 5, add calcium stearate, continue mixing and grinding, and cool to 40°C; Step 6: After crushing and screening, set aside.

[0023] The molding sand properties of this embodiment are as follows: hot tensile strength 1.3Mpa, cold tensile strength 2.5Mpa, hot bending strength ≧2.0Mpa, cold bending strength ≧6Mpa, gas evolution ≤18, and loss on ignition <5%. Example 2

[0024] The weight ratio of the molding sand is: 100 parts of quartz sand, 30 parts of iron sand, 30 parts of waste high-alumina brick particles, 4 parts of phenolic resin, 0.05 parts of silane, 0.7 parts of hexamethylenetetramine and 0.4 parts of calcium stearate; The preparation steps are the same as those in Example 1; The molding sand properties of this embodiment are as follows: hot tensile strength 1.05 MPa, cold tensile strength 2.2 MPa, hot bending strength 2.0 MPa, cold bending strength 6 MPa, gas evolution 18, and loss on ignition 5%.

[0025] The molding sand prepared in Example 1 and Example 2 is used to produce pearlite-based cast iron. Example 3

[0026] The weight ratio of the molding sand is: 100 parts of quartz sand, 25 parts of iron sand, 40 parts of waste high-alumina brick particles, 6 parts of water glass, 0.2 parts of ethylene glycol diethyl ester and 1 part of yellow dextrin; The preparation steps are: Step 1: Put quartz sand, iron sand, yellow dextrin and waste high-alumina brick particles into a sand mixer and mix them for 2 minutes; Step 2: Add water glass and mix for 3 minutes; Step 3: Add ethylene glycol diethyl ether, mix for 1 minute, and use immediately after unloading the sand.

[0027] The properties of the molding sand in this embodiment are as follows: wet compressive strength 0.02 Mpa, dry tensile strength 1.0 Mpa, and it is used for steel casting production. Example 4

[0028] The weight ratio of the molding sand is: 100 parts of quartz sand, 0 parts of iron sand, 10 parts of waste high-alumina brick particles, 4 parts of bentonite, 0.05 parts of sodium carbonate, 4 parts of coal powder and 4.5 parts of water content; The preparation steps are: Step 1: Put quartz sand, bentonite and waste high-alumina brick particles into a sand mixer and mix them for 3 minutes; Step 2: Add sodium carbonate and mix for 3 minutes; Step 3: Add coal powder and water, mix for 2 minutes, and it can be used after mixing.

[0029] The molding sand properties of this embodiment are: green compressive strength 0.08 MPa, wet air permeability 100, and is used to produce ductile iron with a ferrite matrix. Example 5

[0030] The weight ratio of the molding sand is: 100 parts of quartz sand, 40 parts of iron sand, 20 parts of waste high-alumina brick particles, 6 parts of bentonite, 0.1 parts of sodium carbonate, 4 parts of coal powder and 3.5 parts of water content; The preparation steps are the same as those in Example 4; The molding sand properties of this embodiment are as follows: green compressive strength 0.09 MPa, wet air permeability 120, and is used to produce ductile iron with pearlite matrix.

[0031] The present invention can adjust the performance of the molding sand by adding different proportions of iron sand and waste high-aluminum brick particles according to the requirements of the casting during the casting process. The iron sand can adjust the cooling capacity of the molding sand, and the waste high-aluminum brick particles improve the refractoriness of the molding sand, so that the molding sand has the functions of adjusting the refractoriness and cooling speed, thereby solving the problem that it is difficult to obtain high-quality castings with the existing single molding sand.

[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A molding sand with adjustable refractoriness and cooling rate, characterized in that: The specific composition is: quartz sand, iron sand, waste high-alumina brick particles, binder and additives; The binder specifically consists of: one or more of phenolic resin, water glass and clay; The additive specifically consists of: one or more of urotropine, calcium stearate, silane, ethylene glycol diethyl ester, yellow dextrin, sodium carbonate, coal powder, water, calcium stearate, bentonite and sodium carbonate; According to the different binders and additives added, the above materials can be combined into coated sand, water glass sand and clay sand; The waste high-alumina bricks are high-alumina bricks discarded after industrial kilns are replaced. They are crushed into particles and then placed in a drum for processing, so that the waste high-alumina brick particles collide and rub against each other, making the particles polygonal or round in shape, and then sieving to obtain the required particle size.

2. The molding sand with adjustable refractoriness and cooling rate according to claim 1, characterized in that: The weight ratio of the coated sand is: 100 parts of quartz sand, 0-50 parts of iron sand, 2-40 parts of waste high-alumina brick particles, 3-7 parts of phenolic resin, 0.04-0.06 parts of silane, 0.6-1.2 parts of hexamethylenetetramine and 0.3-0.45 parts of calcium stearate.

3. The molding sand with adjustable refractoriness and cooling rate according to claim 1, characterized in that: The weight ratio of the water glass sand is: 100 parts of quartz sand, 0-50 parts of iron sand, 2-40 parts of waste high-alumina brick particles, 3-7 parts of water glass, 0.1-0.5 parts of ethylene glycol diethyl ester and 1.0-2.0 parts of yellow dextrin.

4. The molding sand with adjustable refractoriness and cooling rate according to claim 1, characterized in that: The weight ratio of the clay sand is: 100 parts of quartz sand, 0-50 parts of iron sand, 10-40 parts of waste high-alumina brick particles, 4-6 parts of bentonite, 0.1-0.05 parts of sodium carbonate, 3-6 parts of coal powder and 3.5-5 parts of water content.

5. The molding sand with adjustable refractoriness and cooling rate according to claim 2, characterized in that: The weight ratio of the molding sand is: 100 parts of quartz sand, 0 parts of iron sand, 30 parts of waste high-alumina brick particles, 3 parts of phenolic resin, 0.04 parts of silane, 0.6 parts of hexamethylenetetramine and 0.3 parts of calcium stearate.

6. The molding sand with adjustable refractoriness and cooling rate according to claim 2, characterized in that: The weight ratio of the molding sand is: 100 parts of quartz sand, 30 parts of iron sand, 30 parts of waste high-alumina brick particles, 4 parts of phenolic resin, 0.05 parts of silane, 0.7 parts of hexamethylenetetramine and 0.4 parts of calcium stearate.

7. The molding sand with adjustable refractoriness and cooling rate according to claim 3, characterized in that: The weight ratio of the molding sand is: 100 parts of quartz sand, 25 parts of iron sand, 40 parts of waste high-alumina brick particles, 6 parts of water glass, 0.2 parts of ethylene glycol diethyl ester and 1 part of yellow dextrin.

8. The molding sand with adjustable refractoriness and cooling rate according to claim 4, characterized in that: The weight ratio of the molding sand is: 100 parts of quartz sand, 0 parts of iron sand, 10 parts of waste high-alumina brick particles, 4 parts of bentonite, 0.05 parts of sodium carbonate, 4 parts of coal powder and 4.5 parts of water content.

9. The molding sand with adjustable refractoriness and cooling rate according to claim 4, characterized in that: The weight ratio of the molding sand is: 100 parts of quartz sand, 40 parts of iron sand, 20 parts of waste high-alumina brick particles, 6 parts of bentonite, 0.1 parts of sodium carbonate, 4 parts of coal powder and 3.5 parts of water content.

10. The molding sand with adjustable refractoriness and cooling rate according to claim 2, characterized in that: The preparation steps are as follows: Step 1: Mix quartz sand and waste high-alumina brick particles and heat them to 140-160°C; Step 2: Put the hot sand into the sand mixer and slowly add phenolic resin for 30 to 50 seconds; Step 3: Add silane for 10 seconds; Step 4: Add urotropine aqueous solution, the ratio of urotropine to water is 1:1, and the time is 30 seconds; Step 5, add calcium stearate, continue mixing and grinding, and cool to 40°C; Step 6: After crushing and screening, set aside.